TMIC-37. TARGETING THE EXTRACELLULAR MATRIX OF GLIOBLASTOMAS CHANGES THE POLARIZATION OF TUMOR-ASSOCIATED MACROPHAGES AND INCREASES ANTI-TUMOR INFLAMMATORY RESPONSES. (5th November 2018) - Arivazhagan, Roshini; Nandhu, Mohan; Longo, Sharon; Chin, Lawrence; Viapiano, Mariano
Abstract: Glioblastomas (GBMs) are heavily infiltrated by tumor-associated microglia and macrophages (TAMs), which represent the predominant immune cell population in the tumor and may contribute to GBM progression in response to signals from the tumor cells. Fibulin-3 is an extracellular matrix protein secreted by GBM cells that promotes tumor invasion, angiogenesis, and survival of the GBM stem cell population (GSC) by activation of ADAM17/NFkB signaling. We recently developed a function-blocking antibody ("mAb428.2") against fibulin-3 that inhibits the molecular mechanisms of this protein and reduces GSC viability (Nandhu et al., Clin. Cancer Res. 2018). mAb428.2 (8 days x 30 mg/kg, q24h, IV) exerted a significant anti-tumor effect and prolonged the survival of mice carrying patient-derived GBM xenografts implanted sub-cutaneously (N=8/arm p=0.0032) or intracranially (N=10/arm p=0.0005). Importantly, the cyto-reductive effect of mAb428.2 was accompanied by significant necrosis of the tumor core and increased infiltration of IBA1-positive TAMs. Remarkably, TAMs in anti-fibulin-3-treated tumors showed very little expression of Arginase-1, a bona-fide marker of M2 ("tumor-promoting") polarization. Analysis of gene expression in the TAMs recovered from the tumors confirmed significantly increased expression of inflammatory cytokines (IFN-gamma, IL-1beta, IL-10) and downregulation of M2 markers (CD163, CD206, ARG1), suggesting that mAb428.2 had blocked the usual M2 polarization of TAMs observed in GBMs. Moreover, mAb428.2-treated tumors also showed drastically decreased expression of CSF-1a, an M2-inducing cytokine. Knockdown of fibulin-3 in GSCs also reduced CSF-1a expression, which is likely regulated by fibulin-3 through NFkB signaling. Finally, co-culture of PMA-activated U937 macrophages with GSCs caused a significant decrease of tumor cell viability when mAb428.2 was added to the cultures, suggesting that anti-fibulin-3 treatment enables TAMs to attack tumor cells. Taken together, our results strongly suggest that anti-fibulin-3 and possibly other anti-ECM approaches may induce a marked inflammatory reaction driven by innate immune cells, potentiating anti-tumor therapy.